(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research discusses chili price fluctuations during and after Lebaran in Tanjungpinang City from a political economy perspective. Using a descriptive qualitative approach, this study explores the factors that influenced the price spike before Eid and the price decline afterwards. The findings show that the price of red chili reached Rp105,000/kg before Eid and dropped to Rp55,000/kg afterwards. The main contributing factors were increased demand, distribution disruptions, and dependence on supplies from outside the region. In addition, the lack of local government intervention and the dominant role of market players also affected price stability. This study confirms that chili price fluctuations are not only influenced by market mechanisms, but also by power dynamics and local policies.